Nd2007 2007
DOI: 10.1051/ndata:07255
|View full text |Cite
|
Sign up to set email alerts
|

Excitation functions of alpha-induced nuclear reactions on natural erbium and natural ytterbium targets

Abstract: Yb(α,x) 171,172,177g,178m Lu and nat Yb(α,x) 169,177 Yb were measured up to 38 MeV for application purposes (medical isotope production and charged particle activation analysis). The experimental excitation functions are compared to the theoretical calculations based on the model code ALICE-IPPE. The literature is very poor regarding cross section measurements on erbium or ytterbium irradiated with alpha particles. Yields of different production routes (proton-, deuteron-and alpha-irradiation) of 169 Yb and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…MeV (Király et al, 2007 and the proton induced reactions up to 70 MeV (Hermanne et al, 2011a;Tarkanyi et al, 2016;Tárkányi et al, 2008Tárkányi et al, , 2009 have already been reported by us.…”
Section: Introductionsupporting
confidence: 68%
“…MeV (Király et al, 2007 and the proton induced reactions up to 70 MeV (Hermanne et al, 2011a;Tarkanyi et al, 2016;Tárkányi et al, 2008Tárkányi et al, , 2009 have already been reported by us.…”
Section: Introductionsupporting
confidence: 68%
“…Although the characteristic γ-ray decay line at 320.082 keV has only a moderate intensity of 9.910%, this emission allows an accurate assessment of the 51 Cr activity produced. Fifteen publications with experimental cross-section data within the specified incident particle energy range of interest were identified in the literature [86,211,275,[301][302][303][304][305][306][307][308][309][310][311][312], and are represented with their uncertainties in Fig. 31(a).…”
Section: Crmentioning
confidence: 99%
“…nat Ti(a,x) 51 nat Ti(a,x) 51 Cr [86,211,275,[301][302][303][304][305][306][307][308][309][310][311][312] for the nat Ti(α,x) 51 Cr monitor reaction.…”
Section: Crmentioning
confidence: 99%
See 1 more Smart Citation
“…There is large disagreement between experimental data of Homma 1980 [55], Archenti [56], Sonzogni 1992 [57] and Kiraly 2007 [58] (Fig. 36).…”
Section: Nat Er(xn) 169 Yb Reactionmentioning
confidence: 98%